The health-economic studies of HPV vaccination in Southeast Asian countries: a systematic review - Didik Setiawan; Monika Puri Oktora; Raymond Hutubessy; Arthorn Riewpaiboon; Maarten J. Postma (Taylor & Francis Group, 2017)
Introduction: The cervical cancer-related burden is an important problem in Southeast Asian (SEA) countries. However, only 3 out of 11 countries implement the comprehensive prevention program. Areas covered: This is a retrospective review from all relevant studies until 2015 from two main databases, MEDLINE/Pubmed and Embase in order to provide an evidence on the health economics of HPV vaccination in the region. Expert commentary: The implementation of HPV vaccination will generate substantial health and economic benefit in SEA countries since the number of cervical cancer cases in this region are generally high. Therefore, a clear recommendation on how HPV vaccination should be implemented in a country, for example on how many doses will be used, how much cost is required or is it a school based- or clinical based-delivery, is critically required.